2022
DOI: 10.3389/fmed.2022.760816
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on Multiplate®-, ROTEM®- and Thrombin Generation Examinations Before and Early After Implantation of a Left Ventricular Assist Device (LVAD)

Abstract: BackgroundHeart failure patients are frequently on coagulation-active medications before LVAD implantation and perioperative bleeding is a frequent complication after left ventricular assist device (LVAD) implantation. The role of point-of-care coagulation tests in assessing bleeding risk for LVAD implantation and the early postoperative time course of these tests is not well established.MethodsWe prospectively enrolled 25 patients with terminal heart failure undergoing LVAD implantation. Study related TRAP-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It was shown that the severity of acquired platelet defects, i.e., reduced GPIbα and GPVI expression and reduced α IIb β 3 activation, is predictive of non-surgical bleeding events in CTD recipients, having even higher predictive power than vWF degradation parameters [ 37 ]. Further, device-implanted patients with increased bleeding risk demonstrate decreased platelet aggregation response, underscoring the importance of these acquired defects as drivers of device-related bleeding coagulopathy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the severity of acquired platelet defects, i.e., reduced GPIbα and GPVI expression and reduced α IIb β 3 activation, is predictive of non-surgical bleeding events in CTD recipients, having even higher predictive power than vWF degradation parameters [ 37 ]. Further, device-implanted patients with increased bleeding risk demonstrate decreased platelet aggregation response, underscoring the importance of these acquired defects as drivers of device-related bleeding coagulopathy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…80 It was also reported that device-implanted patients with increased bleeding risk demonstrate decreased platelet aggregation response to biochemical agonists (ADP, TRAP-6, and arachidonic acid), underscoring the importance of these acquired defects as drivers of device-related bleeding coagulopathy. 138…”
Section: Discussionmentioning
confidence: 99%
“…80 It was also reported that deviceimplanted patients with increased bleeding risk demonstrate decreased platelet aggregation response to biochemical agonists (ADP, TRAP-6, and arachidonic acid), underscoring the importance of these acquired defects as drivers of device-related bleeding coagulopathy. 138 Routine flow cytometry used to capture and characterize shear-mediated PDMPs is known to underestimate the small-size microparticle population (<300 nm) and exosomes (<100 nm). Therefore, the number of shear-ejected microvesicles detected in our study might also be underestimated.…”
Section: C-d)mentioning
confidence: 99%
“…The impact of LVAD implantation on patients’ plasmatic coagulation system is challenging to investigate due to additional altering factors, particularly surgery itself and required anticoagulation ( 23 ). Thrombin generation before and after LVAD implantation has been examined in a recent study ( 24 ). However, the authors focused on longitudinal progression and did not antagonize heparinized samples.…”
Section: Discussionmentioning
confidence: 99%